Reformasi Kultural Orde Baru dalam Perspektif Postmodernisme - Arinto Nurcahyono (Unisia, 1999)
As a discourse of Postmodernism, deconstruction has a great importance to be used as a tool of cultural reform in Indonesia. When The New Era was in power it developed the "logocentrism culture" through the creation of "biner position" in the structure of language, society, political-economy, and of course, culture. These structures were implemented in the feudalism., totalitarianism, and oppresive manner of the New Era. The stigmatization against some groups as a subversives, dissident or anti-Pancaslla, had been very popular during Suharto's regime. Hopefully, the deconstruction perspective, as a tool of reform will encourage changes in Indonesia which meet requirements for globalization. Finally, it recommended that the perspective of deconstruction encourage changes for Indonesia toward the new paradigm and structure which, in turn, satisfy, the intemal and global needs.